PENINGKATAN KEMAMPUAN BERBICARA DENGAN MENGGUNAKAN METODE STORYTELLING PADA PEMBELAJARAN BAHASA INDONESIA - Mulyono, Dedi; Yufiarti, Yufiarti; Yarmi, Gusti (Jurnal Pendidikan Dasar, 2018)
Abstract:This study aims to improve the ability to speak with the adoption of storytelling the third classin Private Elementary Schools Darussalam Cirebon in the academic year 2017/2018. This research is an action using Action Research Model Kemmis and McTaggart. This study was conducted in two cycles with the first cycle consisted of three meetings, and the second cycle consists of 4 meetings. Each cycle do the planning, action, observation and reflection. This research was conducted there whole third grade students. The instrument used to collect data by observation, tests, interviews, and documentation. Monitoring data analysis actions are performed after the data collected will be through checking the completeness of data, data collection, data analysis techniques and descriptive with percentage. The results showed that learning the Indonesian language with storytelling method implementation can enhance the ability to speak. This is indicated from the observed activities and positive response from the students as a whole against the Indonesian language learning with the adoption of storytelling.As well as by an increase in students' speaking ability scores on each indicator and the value end of the cycle test all students in grade III. The increase in value in the first cycle the number of students who were able to achieve success indicator is only 57.70% of the students, and increased in the second cycle into 88.50% of students Keywords: Speech,Method Storytelling